2016
DOI: 10.1016/j.rmed.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyponatremia on mortality and morbidity in patients with COPD exacerbations

Abstract: Hyponatremia is the most common electrolyte disorder in hospitalized patients, being associated with increased morbidity and mortality in different clinical conditions. However, the prevalence and impact of this electrolytic disorder in patients hospitalized for an exacerbation of COPD still remains unknown. The aim of the present study was to clarify these points. A total of 424 patients hospitalized due to a COPD exacerbation were consecutively included, showing a frequency of hyponatremia of 15.8% (hyposmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 55 publications
0
33
1
1
Order By: Relevance
“…We have presented in generally great detail, the diagnostic and therapeutic complexities involved in the management of hyponatremia especially when this is complicated by co-existing pulmonary edema, acutely decompensating heart failure and pulmonary hypertension in the context of advanced COPD. We were able to achieve excellent 'diuresis' using the aquaresis-inducing properties of intravenous conivaptan, an ADH antagonist (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Notedly, dyspnea, edema and volume overload promptly resolved as confirmed by follow up symptomatic relief, resolution of physical examination findings and improvement evident in the follow up chest radiograph (Figure 1).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…We have presented in generally great detail, the diagnostic and therapeutic complexities involved in the management of hyponatremia especially when this is complicated by co-existing pulmonary edema, acutely decompensating heart failure and pulmonary hypertension in the context of advanced COPD. We were able to achieve excellent 'diuresis' using the aquaresis-inducing properties of intravenous conivaptan, an ADH antagonist (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Notedly, dyspnea, edema and volume overload promptly resolved as confirmed by follow up symptomatic relief, resolution of physical examination findings and improvement evident in the follow up chest radiograph (Figure 1).…”
Section: Discussionmentioning
confidence: 81%
“…Finally, treatment with intravenous conivaptan facilitated improvement of severe symptomatic hyponatremia in our patient, and simultaneously, the resulting aquaresis led to a rapid and sustained improvement in his dyspnea from pulmonary edema. There is accruing evidence in the literature that the vaptans, intravenous conivaptan and oral tolvaptan, have now earned a place in the therapeutic armamentarium to manage symptomatic acutely decompensating heart failure complicated by severe hyponatremia and volume overload (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Subsequently, the administration of loop diuretics appears to be usually well tolerated without necessarily a need for the prolonged use of the vaptans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 28.6% of neurological pathologies, 20.2% of renal pathologies and 5.1% of cardiac pathologies. Several authors have reported that diseases of the central nervous system constitute the main etiologies of hyponatremia [15,16]. This is explained by the alteration of the tubular reabsorption of sodium which is manifest during a cerebral lesion thus decreasing the sodic pool of the organism [15].…”
Section: Discussionmentioning
confidence: 99%